Photovoltaic-supported hybrid atmospheric water harvesting systems: comparative performance analysis of different configurations - Kamil Neyfel Çerçi (Case Studies in Thermal Engineering)
This study presents a first-time comparative performance analysis of eight photovoltaic-supported hybrid atmospheric water harvesting (AWH) configurations that integrate desiccant wheels, heat exchangers, and vapor-compression refrigeration (VCR) units, using low-GWP refrigerants. The novel hybrid design combines desiccant-assisted dehumidification, internal heat recovery, and renewable energy to enhance water yield while minimizing electricity demand. Key performance metrics, such as coefficient of performance (COPr), second-law efficiency (η2,c), water harvesting efficiency (WHE), and required PV panel area, were evaluated under varying regeneration temperatures, airflow rates, and climate zones. Among all setups, Configuration 8, featuring two-stage desiccant wheels, a heat exchanger, and waste heat utilization, consistently delivered the best performance with the lowest energy consumption and highest WHE. Under typical summer conditions in Mersin, this configuration yielded approximately 17 L/day of water. Furthermore, it performed best in the Warm and Moderately Humid (W&MH) climate zone, offering an optimal balance between water recovery and energy efficiency. The main advantage of the method lies in its energy-efficient operation and adaptability to different climatic conditions. Additionally, utilizing condenser waste heat reduced electricity demand by up to 67 %. This hybrid system offers a practical and sustainable solution for decentralized water production in water-scarce regions.